Nexus between Corporate Governance Measures and Firm Performance: Evidence from a Fastest Growing Economy - Maniruzzaman, Md.; Hossain, Syed Zabid (Indonesian Journal of Sustainability Accounting and Management, 2024)
This research strived to examine the impacts of corporate governance practices on firm performance in Bangladesh. The study used data from DSE-listed manufacturing firms from 2007 to 2020 to run a panel regression model with Tobin’s Q and ROA to catch the effects of CG norms on firm performance. Board size, firm age, and ownership concentration positively and significantly affect firm performance. However, gender diversity, CEO duality, financial leverage, SEC guidelines, and firm size have a negative affinity for performance, and all are significant except CEO duality. The study extends the literature by feeding new academic insights and answering the questions on the logical grounds of why and why not hypotheses are accepted. No prior literature focused on the impacts of CG norms on firm performance in light of the mandatory CG guidelines 2012. Hence, the results have led to an academic debate on the effectiveness of the CG guidelines.